Bioenergy production and sustainable development: science base for policymaking remains limited. Issue 3 (23rd March 2016) - Robledo‐Abad, Carmenza; Althaus, Hans‐Jörg; Berndes, Göran; Bolwig, Simon; Corbera, Esteve; Creutzig, Felix; Garcia‐Ulloa, John; Geddes, Anna; Gregg, Jay S.; Haberl, Helmut; Hanger, Susanne; Harper, Richard J.; et al.
Abstract: The possibility of using bioenergy as a climate change mitigation measure has sparked a discussion of whether and how bioenergy production contributes to sustainable development. We undertook a systematic review of the scientific literature to illuminate this relationship and found a limited scientific basis for policymaking. Our results indicate that knowledge on the sustainable development impacts of bioenergy production is concentrated in a few well‐studied countries, focuses on environmental and economic impacts, and mostly relates to dedicated agricultural biomass plantations. The scope and methodological approaches in studies differ widely and only a small share of the studies sufficiently reports on context and/or baseline conditions, which makes it difficult to get a general understanding of the attribution of impacts. Nevertheless, we identified regional patterns of positive or negative impacts for all categories – environmental, economic, institutional, social and technological. In general, economic and technological impacts were more frequently reported as positive, while social and environmental impacts were more frequently reported as negative (with the exception of impacts on direct substitution of GHG emission from fossil fuel). More focused and transparent research is needed to validate these patterns and develop a strong science underpinning for establishing policies and governance agreements that prevent/mitigate negative and promote positive impacts from bioenergy production.